Achieving long-term success in irrigation commons - Ulrich J. Frey; Atul Pokharel (PLoS ONE, 2026)
Which characteristics predict the long-term performance and persistence of irrigation systems? This question has been challenging to answer due to the lack of longitudinal data. Numerous cross-sectional studies have identified a wide range of relevant factors. However, it is unclear which of these factors remain associated with long-term persistence, or what their relative predictive power is. To examine performance and survival after a period of 16–37 years with respect to concerning initial system attributes, we have created a unique longitudinal dataset of 218 community-based irrigation systems in Nepal, separated by three decades. We applied the best available models using several state-of-the-art machine learning algorithms to ensure method independence. Our findings show that farmer-managed systems that receive external support and whose leaders are users perform best. Long-term survival is associated with fair rules, regular member meetings, and occasional external assistance. Good institutional design is consistently among the strongest predictors of long-term performance and persistence in irrigation commons.